2020
DOI: 10.1093/ndt/gfaa142.p0141
|View full text |Cite
|
Sign up to set email alerts
|

P0141kidney Biopsy Indications and Outcomes: Seven Years Experience of a Single Centre in Sri Lanka

Abstract: Background and Aims Histopathological analysis of renal biopsy is the cornerstone of diagnosis in renal disease and guides treatment and prognosis. The prevalence of various renal diseases varies according to the geographical area, socioeconomic condition, race, age, demography and indication of renal biopsy. Method A retrospective study of all native and transplant kidney biopsies performed at the renal unit of Sri Jayewarde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The epidemiology of primary and secondary glomerular diseases may differ within the nation due to different socio-economic and ethnic backgrounds in different parts of the country. Similar to our findings, single center studies conducted in Sri Lanka showed nephrotic range proteinuria as the most common indication for renal biopsy [ 27 , 28 ]. Comparably studies done in other parts of the world including Bangladesh [ 29 ], Africa [ 30 ], India [ 15 ], Poland [ 31 ], China [ 32 ] and Romania [ 33 , 34 ] showed nephrotic range proteinuria as the most prevalent indication for renal biopsy.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The epidemiology of primary and secondary glomerular diseases may differ within the nation due to different socio-economic and ethnic backgrounds in different parts of the country. Similar to our findings, single center studies conducted in Sri Lanka showed nephrotic range proteinuria as the most common indication for renal biopsy [ 27 , 28 ]. Comparably studies done in other parts of the world including Bangladesh [ 29 ], Africa [ 30 ], India [ 15 ], Poland [ 31 ], China [ 32 ] and Romania [ 33 , 34 ] showed nephrotic range proteinuria as the most prevalent indication for renal biopsy.…”
Section: Discussionsupporting
confidence: 91%
“…The most frequent histopathological diagnosis in our study was FSGS (22.1%) followed by lupus nephritis (20%), PSGN (17.1%), DN (12.1%), HTN (9.3%), MCD (6.4%), IgA nephropathy (5.7%), IN (4.3%), Vasculitis (2.1%), and MGN (0.7%). Interestingly, primary GN was the most common finding and IgA nephropathy being the most frequent diagnosis in the study performed at Sri Jayewardenepura General Hospital, Sri Lanka between 2012 and 2019 [ 27 ]. However, this does not correspond with our data, which showed FSGS to be the leading cause.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations